2005
DOI: 10.1016/j.transproceed.2005.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Do Elderly Patients Deserve a Kidney Graft?

Abstract: Purpose. Compare renal transplant long-term outcomes among recipients aged 60 years or older with those in younger patients. Patients and methods. We analyzed 103 transplants in recipients above 60 years of age for the influence of key factors related to the graft and patient. The results were compared with 1060 transplant recipients aged 18 to 59 years. Results. The mean ages were 62.93 and 40.35 years for the older and younger group. The older group showed a higher prevalence of obesity and unknown etiologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…The majority of these patients (∼90%) were maintained on commonly used modern immunosuppressive therapies including tacrolimus, mycophenolate mofetil, or sirolimus. Our findings are similar to previous reports, in which patients over the age of 60 exhibited a similar renal function and death‐censored graft survival compared to younger adult patients (4, 8). We observed a significantly lower rate of DGF in the >60 patients which occurred despite the increased use of ECD kidneys among this age group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of these patients (∼90%) were maintained on commonly used modern immunosuppressive therapies including tacrolimus, mycophenolate mofetil, or sirolimus. Our findings are similar to previous reports, in which patients over the age of 60 exhibited a similar renal function and death‐censored graft survival compared to younger adult patients (4, 8). We observed a significantly lower rate of DGF in the >60 patients which occurred despite the increased use of ECD kidneys among this age group.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported lower mortality rates and improved quality of life in renal transplant patients with advanced age compared to those who remain on dialysis (2,3). In addition, short-term outcomes in older recipients are comparable to those in younger patients (4)(5)(6)(7)(8). Thus, kidney transplantation remains the treatment modality of choice in patients with end-stage renal disease (ESRD), regardless of age.…”
Section: Rabbit Antithymocyte Induction and Dosing In Deceased Donor mentioning
confidence: 99%
“…Other studies have also failed to demonstrate statistically significant differences in the incidence of acute rejection between younger and older recipients both in Europe [10][11][12] and in the United States [6,13]. Nonetheless, other authors have reported that elderly patients may have a lower risk of acute rejection compared with younger recipients [14,15], a phenomenon supported by some data suggesting that metabolism of immunosuppressive medications may be altered with increased age [16].…”
Section: Discussionmentioning
confidence: 99%
“…Among the treatment modalities that are available for patients with ESRD, KT is preferred because it is associated with an improved life expectancy, better quality of life, and is cost-effective both for patients and for payers (1-4, 7-15, 18-25, 31-42). However, with the increasing disparity between the steadily rising number of potential transplant candidates and relatively static number of available organs, ethical concerns have been expressed that providing elderly patients with ESRD with scarce DD kidneys may result in significant limitations imposed on the useful life of donor organs (3,4,(20)(21)(22)(23)(24)(25)(37)(38)(39)(40)(41). However, a number of studies have demonstrated that KT offers both a cost and survival benefit to virtually all patients with ESRD regardless of age (3,4,7,8,(18)(19)(20)(21)(22)(23)(24)(25)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%